Gallstone disease and risk of conventional adenomas and serrated polyps: a prospective study - Polychronidis, Georgios; Wang, Kai; Lo, Chun-Han; Wang, Liang; He, Mingming; Knudsen, Markus D.; Wu, Kana; Joshi, Amit D.; Ogino, Shuji; Giovannucci, Edward L.; Chan, Andrew T.; Song, Mingyang (Cancer epidemiology, biomarkers & prevention, 2021)
Background: Gallstone disease has been associated with colorectal cancer and some form of polyps, although the findings are inconclusive. It remains unknown whether gallstone disease influences the initiation of colorectal cancer. - Methods: We prospectively assessed the association of gallstone disease with risk of colorectal cancer precursors, including conventional adenomas and serrated polyps, in the Nurses' Health Study (1992-2012), the Nurses’ Health Study II (1991-2011), and the Health Professionals Follow-up Study (1992-2012). Gallstone diseases were assessed using biennial follow-up questionnaires. Self-reported polyp diagnosis was confirmed by review of medical records. Logistic regression models were used to calculate the ORs with adjustment for smoking and other potential confounders. - Results: Among participants who had undergone a total of 323,832 endoscopies, 16.5% had gallstone disease and 11.3% received cholecystectomy. We documented 1,724, 1,212, and 1,943 cases of conventional adenomas and 1,470, 1,090, and 1,643 serrated polyps in patients with gallstones, cholecystectomy, and either of them, respectively. The OR for adenomas was 1.00 [95% confidence interval (CI): 0.95-1.06] for gallstones, 0.99 (95% CI, 0.93-1.06) for cholecystectomy, and 1.00 (95% CI, 0.95-1.05) for either exposure. The corresponding ORs for serrated polyps were 0.98 (95% CI, 0.92-1.04), 0.99 (95% CI, 0.93-1.06), and 0.97 (95% CI, 0.92-1.03), respectively. - Conclusions: Gallstone disease is not associated with colorectal polyps. - Impact: Patients with gallstones appear to have similar risk of colorectal polyps compared with those without and may therefore follow average-risk colorectal cancer screening guidelines.
Gesehen am 20.01.2022